he correlation between HPV infection and p53, pRb, KI-67 as well as tunnel expression of cervical carcinoma - Irianiwati Ahmad Ghozali Endang Soetristi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: HPV infection has an important role in cell proliferation and apoptosis of malignant neoplasia through the binding of their E6 and E7 protein to the p53 and pRb. In cervical cancer the role of HPV infection in cells proliferation and apoptosis has not yet been defined up to now, since mutation of p53 gene and Rb gene in cervical cancer is very rare.Methodes: Thirty-eight block parafin cases of squamous cell carcinoma of the cervix were stained immunohistochemically with polyclonal antibody against HPV and monoclonal antibody against p53, Rb, Ki-67 and Tunnel. with chromogen DAB and counterstain Hematoxyllin Meyer. The expression of HPV, p53, pRb, Ki-67 and Tunnel were counted based on the number of positive cells/100 tumor cells in five microscopic fields. The correlation between HPV expression and p53, pRb, Ki-67, Tunnel expression respectively were analyzed with Pearson correlation analysis.Results: There was a significant correlation between HPV expression with either p53 expressionR: 0.491, P:0.002) and or Ki-67 expression (R:0.397, P:0.014), but there was no significant correlation between HPV expression with pRB expression (R:0.3000, P:0.067) and Tunnel expression ( R:O,888, P:0,599).Conclusion: This research showed that HPV infection had important role in cell proliferation but not in cell apoptosis of cervical cancer.Key words: HPV, proliferation, apoptosis, p53, pRb, Ki-67, Tunnel, cervical carcinoma